2023
DOI: 10.1039/d2ta08777d
|View full text |Cite
|
Sign up to set email alerts
|

Rational design and regulation of tremella-like selenium-doped MoS2 for highly reversible sodium storage

Abstract: Molybdenum disulfide (MoS2), due to its high theoretical specific capacity (670 mAh g-1), has evoked considerable investigation interest regarding Na+ storage. Nonetheless, the irreversible conversion of original material MoS2 into...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…11c display the out-of-plane (A1g) (238 cm -1 ) and in-plane (E 2g 1 ) (283 cm -1 ) vibrational modes of Mo-Se. There is no obvious detection of signals of Mo-S out-of-plane (A1g) and in-plane (E 2g 1 ) at ~400 cm -1 , reflecting that the amount of doped S in the system is low [7]. It was observed that the strength ratio of (A1g) to (E 2g 1 ) in C@MoSe2(12.26)、 C@MoSe2(1-x)S2x@MWCNT (14.31) and PEG-200-2-C@MoSe2(1-x)S2x@MWCNT (13.82) are rather close, which confirms that the coating of carbon on MoSe2(1-x)S2x@MWCNT does not adversely affect the layered structure of the three samples [7,33].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…11c display the out-of-plane (A1g) (238 cm -1 ) and in-plane (E 2g 1 ) (283 cm -1 ) vibrational modes of Mo-Se. There is no obvious detection of signals of Mo-S out-of-plane (A1g) and in-plane (E 2g 1 ) at ~400 cm -1 , reflecting that the amount of doped S in the system is low [7]. It was observed that the strength ratio of (A1g) to (E 2g 1 ) in C@MoSe2(12.26)、 C@MoSe2(1-x)S2x@MWCNT (14.31) and PEG-200-2-C@MoSe2(1-x)S2x@MWCNT (13.82) are rather close, which confirms that the coating of carbon on MoSe2(1-x)S2x@MWCNT does not adversely affect the layered structure of the three samples [7,33].…”
Section: Resultsmentioning
confidence: 99%
“…After the second cycle, the peak at 1.4 V (discharging) is related to the conversion of MoSe2(1-x)S2x to Mo and Na2Se (Na2S). Peaks at 1.69 V (charging) is related to the conversion of Na2Se (Na2S) to Se (S), and oxidation of Mo (MoSe2(1-x)S2x) [7,27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the high-temperature synthesis often damages the defect sites that are crucial for catalytic activity, leading to suboptimal performance. While the solvothermal method can produce MoS x Se 2– x with a high density of defects at relatively lower temperatures, enhancing its HER activity, the process involves hazardous steps and the use of toxic Se compounds, which hinders its industrial feasibility. To date, developing a simple and scalable synthesis method for defective MoS x Se 2– x , suitable for mass production and broad application, remains a significant challenge.…”
Section: Introductionmentioning
confidence: 99%
“…1–4 To date, various TMSs ( e.g. , CoS 2 , 5,6 ZnS, 7,8 Ni 3 S 2 , 9 NiS 2 , 10,11 and MoS 2 12,13 ) have been extensively researched as next-generation anodes of sodium-ion batteries (SIBs). Among them, nontoxic ZnS attracts a lot of attention due to its low working potential (<1.0 V, vs. Na/Na + ) and relatively high theoretical capacity (about 581.4 mA h g −1 ).…”
Section: Introductionmentioning
confidence: 99%